Caecal endometriosis presenting with an acute abdomen in pregnancy. Issue 9 (21st September 2022) - Dunphy, Louise; Furara, Samira; Swaminathan, Ajay; Howe, Rachael; Ali Kazem, Mohammed; Kyriakidis, Dimitrios
Abstract : Endometriosis is defined as the presence of endometrial tissue outside the uterus, which induces a chronic inflammatory response. Its prevalence remains unknown, but it has been estimated to affect up to 10% of women of reproductive age. Although it is a benign oestrogen-dependent gynaecological condition, women may describe painful symptoms such as cyclical pelvic pain, dysmenorrhoea and dyschezia. Intestinal endometriosis may affect the ileum, appendix, sigmoid colon and rectum. It may present with a myriad of symptoms such as abdominal pain, vomiting, diarrhoea, constipation and haematochezia. Caecal endometriosis can present as an acute appendicitis, making the diagnosis challenging to establish in pregnancy. Transmural involvement and acute occlusion are very rare events. The gold standard for diagnosis remains laparoscopy with tissue sampling for histological confirmation. Although endometriosis improves during pregnancy under the effect of progesterone, the ectopic endometrium becomes decidualised with a progressive reduction in size. The authors present the case of a multiparous woman in her mid-30s with acute onset of right-sided abdominal pain at 35 weeks gestation. Physical examination was suggestive of an acute appendicitis and MRI showed an inflamed caecum. She became acutely unwell requiring an emergency caesarean section. A mass in the caecum was observed with impending perforation at the caecal pole. A right hemicolectomy was performed. Histopathological examination confirmed the diagnosis of endometriosis with decidualisation. Although endometriosis improves during pregnancy, this case shows the unexpected complications of the disease and demonstrates the importance of considering endometriosis in the differential diagnosis of an acute abdomen in women of childbearing age to prevent maternal morbidity and fetal loss.